1958
DOI: 10.1111/j.1365-246x.1958.tb05351.x
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-static Motions near the San Andreas Fault Zone

Abstract: Summary A technique is presented for computing quasi‐static strains and displacements at the surface of a vertically heterogeneous elastic or viscoelastic half‐space caused by a dislocation of finite size. The distribution of displacement discontinuity and orientation of the dislocation surface are arbitrary. The technique is applied to the problems of deep stress relaxation on the San Andreas fault. It is found that modern geodetic data do not allow ready distinction between stress relaxation due to deep seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…Some of the following is taken from Singh [ 1970] and Jooannooich et al [1974a] (see also Barker [1976] As will be shown here, however, this is not necessary; and although the integration is done only for a single layer over a half space, the generalization to many layers is again obvious.…”
Section: Elastic Green Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the following is taken from Singh [ 1970] and Jooannooich et al [1974a] (see also Barker [1976] As will be shown here, however, this is not necessary; and although the integration is done only for a single layer over a half space, the generalization to many layers is again obvious.…”
Section: Elastic Green Functionsmentioning
confidence: 99%
“…Recent years have seen the growth of a great deal of interest in modeling the transient quasi-static motions of the earth's surface [Nur and Mavko, 1974;Peltier, 1974;Melosh, 1976;Barker, 1976;Rundle, 1976;Rundle and Jackson, 1977a, b, c]. There has been a recognition that the examination of the available crustal strain data, heat flow transients, aftershock migration patterns, and so on may reveal much about the causes and mechanisms of flow and stress relaxation within the earth.…”
Section: Introductionmentioning
confidence: 99%
“…Triangles denote individual stations, and dark lines enclose regions within which uniform strain fields have bccn fit to the angle change data. Principal active right-lateral faults arc shown, and circled dots locate epicenters ooe significant earthquakes Barker, 1976],. where it has bccn either assumed that the 1941/ , 54 straining represented normal secular deformation or concluded on the basis of less-than-complete analysis that deformation was uniform during the entire 1941-1967 interval Whitten's [1960].…”
mentioning
confidence: 99%
“…We now apply these models to the northern 'locked' segment of the San Andreas fault and try a numerical estimate of some of the quantities involved in the model. We use throughout a = 10 km for the maximum fault depth [see, e.g., Barker, 1976] and /x = 3 x 10 • dyne/cm 2 for the shear modulus. As stated above the models are intended to apply to the fault region.…”
Section: Ah(x3 T) = Vto(x3 --Z)mentioning
confidence: 99%